A Pilot Study of Real Time Elastography in the Differentiation of Focal Liver Lesions - Sandulescu, Larisa (Medical University Publishing House Craiova, 2012)
Introduction: Real time-sonoelastography (RTE) is a new developed technique that reveals the physical properties of the tissue by characterizing the difference in hardness between diseased tissue and surrounding tissue. Elasticity measurements have been already reported to be useful for the diagnosis and differentiation of many tumors: breast lesions, prostate cancer, lymph nodes and pancreatic masses but there are only few studies for the focal liver lesions. The aim of the study was to analyze whether computer enhanced dynamic analysis of elastography images is able to better characterize and differentiate benign and malignant liver lesions. Material and methods: The study group included, in total thirty nine liver tumors. RTE was performed by EUS or transabdominal ultrasound. ROC analysis for the mean hue obtained through histogram analysis of the region of interest (liver lesion) after averaging individual pixels over a 10-second elastography movies was used to assess the color information inside the region of interest and to consequently differentiate benign and malignant liver lesions. Based on a cutoff of 170 for the mean hue histogram values recorded on the region of interest, the sensitivity, specificity, and accuracy of differentiation of benign and malignant masses were 92.5%, 88.8%, and 88.6%, respectively. The positive and negative predictive values were 86.7% and 92.3%, respectively. In conclusion, real time sonoelastography is a promising technique that might improve the characterization and differentiation between benign and malignant focal liver lesions visualized during transabdominal or endoscopic ultrasound.